Telephone-Delivered Exercise Advice and Behavior Change Support by Physical Therapists for People With Knee Osteoarthritis: Protocol for the Telecare Randomized Controlled Trial - Hinman, R.; Lawford, B.; Campbell, P.; Briggs, Andrew; Gale, J.; Bills, C.; French, S.; Kasza, J.; Forbes, A.; Harris, A.; Bunker, S.; Delany, C.; et al. (American Physical Therapy Association, 2017)
Background.: Exercise and physical activity are a core component of knee osteoarthritis (OA) care, yet access to physical therapists is limited for many people. Telephone service delivery models may increase access. Objective.: Determine the effectiveness of incorporating exercise advice and behaviour change support by physical therapists into an existing Australian nurse-led musculoskeletal telephone service for adults with knee OA. Design.: Randomized controlled trial with nested qualitative studies. Setting.: Community, Australia-wide. Participants.: 175 people =45 years with knee symptoms consistent with a clinical diagnosis of knee OA. Eight musculoskeletal physical therapists will provide exercise advice and support. Intervention.: Random allocation to receive existing care or exercise advice in addition to existing care. Existing care is a minimum of one phone call from a nurse for advice on OA self-management. Exercise advice involves 5-10 calls over 6 months from a physical therapist trained in behaviour change support to prescribe, monitor and progress a strengthening exercise program and physical activity plan. Measurements.: Outcomes will be measured at baseline, 6 and 12 months. Primary outcomes are knee pain and physical function. Secondary outcomes include other measures of knee pain, self-efficacy, physical activity and its mediators, kinesiophobia, health service usage, work productivity, participant-perceived change and satisfaction. Additional measures include adherence, adverse events, therapeutic alliance, satisfaction with telephone-delivered therapy and expectation of outcome. Semi-structured interviews with participants with knee OA and therapists will be conducted. Limitations.: Physical therapists cannot be blinded. Conclusions.: This study will determine if incorporating exercise advice and behaviour change support by physical therapists into a nurse-led musculoskeletal telephone service improves outcomes for people with knee OA. Findings will inform development and implementation of telerehabilitation services.